2008
DOI: 10.1063/1.2872941
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of phase separating binary liquids in cylindrical Couette flow

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…At the polymer-solvent interface, for r Ϸ 52 , the velocity profile shows a steep drop, indicative of a significant degree of slippage. Rod-solvent and even solvent-solvent 34 systems show similar hallmarks of slippage at their interfaces. It might be argued that the partial nonstick boundary condition is exacerbated by the purely repulsive interactions between unlike particles, which weakens the mutual grip of the two fluids.…”
Section: -7mentioning
confidence: 85%
See 4 more Smart Citations
“…At the polymer-solvent interface, for r Ϸ 52 , the velocity profile shows a steep drop, indicative of a significant degree of slippage. Rod-solvent and even solvent-solvent 34 systems show similar hallmarks of slippage at their interfaces. It might be argued that the partial nonstick boundary condition is exacerbated by the purely repulsive interactions between unlike particles, which weakens the mutual grip of the two fluids.…”
Section: -7mentioning
confidence: 85%
“…Theoretical expressions for the interfacial shape in a Couette cell have been derived in Ref. 34, where it was found that the surface tensions consistently enter the expressions in the form ⌫ = ͑␥ AW − ␥ BW ͒ / ␥ AB , with A, B, and W denoting the two fluids and the wall, respectively. For a -stack, for instance, the interface is described by…”
Section: B Steady State At Zero Shearmentioning
confidence: 99%
See 3 more Smart Citations